An electroluminescent material based on pyridine-3,5-dicarbonitrile and its application in organic light-emitting devices
By introducing luminescent material compounds that heat-activate the reverse RISC process into the organic luminescent material, the problems of limited efficiency and high cost of organic electroluminescent materials in the prior art are solved, and an efficient and low-cost organic luminescent effect is achieved.
Patent Information
- Application Number
- CN202110188558.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-02-19
AI Technical Summary
The internal quantum efficiency of existing organic electroluminescent materials is limited, with the efficiency of traditional fluorescent materials up to 25%, while metal complex phosphorescent materials are costly and have poor color standard design flexibility. Although TADF materials have high theoretical efficiency, their actual performance is Far less than TADF materials based on 1,3,5-triazine.
Using a new organic luminescent material, the luminescent material compounds in its luminescent layer are used to generate fluorescence by thermally activating the reverse RISC process, and transitioning from singlet state S1 to ground state S0 and triplet state T1 to S1 and then transitioning to ground state S0 to generate fluorescence. Avoid the use of precious metals.
The luminous effect with high purity luminous tone, high luminous efficiency and long life is achieved, while reducing production costs, providing an alternative to traditional blue fluorescent materials and metal phosphorescent materials.
Smart Images

Figure CN113224247B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to organic electroluminescent materials and devices, and more specifically to a light-emitting device driven by an electric field and a thin film formed by a reverse intersystem crossing thermally activated delayed RISC light-emitting material and an organic semiconductor light-emitting compound. Background Art
[0002] An organic electroluminescent device (OLED) includes a pair of electrodes forming an anode and a cathode, and one or more layers of materials consisting of a hole injection layer, an emission layer, an electron transport layer and some other charge layers, wherein the emission layer is composed of a light-emitting compound dopant and a host material.
[0003] Traditional organic electroluminescent devices (OLEDs) are devices with a simple structure of fluorescent material dopants. The maximum internal quantum yield of such fluorescent OLEDs is widely believed to be theoretically limited to less than 25%. The fluorescent material is often defined as the first generation of light-emitting materials, and the light-emitting device composed of it is called the first generation of OLEDs.
[0004] As the second generation of luminescent materials, phosphorescent materials have been proven to be widely used luminescent material dopants for OLED by utilizing triplet states to improve quantum yield. Phosphorescent dopants are basically precious metal complexes that can cause metal-d orbital interactions, and their theoretical internal quantum efficiency can reach 100% (Appl. Phys. Lett., 1999, 75, 4-6.). However, the phosphorescent metal complex materials using iridium metal and rare metals are expensive and have manufacturing cost problems. In addition, due to the ligand structure dependence of the complex, the design flexibility of the phosphorescent luminescent color is also limited, and the iridium complex is not necessarily thermally stable.
[0005] As the third generation of organic light-emitting materials, TADF (Thermally activated delayed fluorescence) materials have attracted extensive attention and become a research hotspot because of their ability to utilize triplet excitons to participate in electroluminescence through the reverse inter-system conversion (RISC) process (US 7034454, JP 3848306, JP 3848307) and theoretically achieve 100% maximum exciton utilization.
[0006] The T1 of TADF material is close enough to S1, and the T1 energy level is lower than S1, and allows the T1 exciton to be converted into radiative S1 exciton through thermally activated reverse intersystem crossing RISC (Appl. Phys. Lett., 2012, 101, 093306.). Therefore, the theoretical internal quantum efficiency of TADF can reach 100%.
[0007] Compared with traditional fluorescent materials (first-generation organic light-emitting materials), TADF materials have higher electroluminescent efficiency because they can achieve 100% internal quantum efficiency; on the other hand, compared with metal complex phosphorescent materials, TADF materials have huge cost and stability advantages because they do not require the use of rare precious metals.
[0008] Pyridine-3,5-dicarbonitrile and 1,3,5-triazine have similar electron-absorbing properties, and the cyano groups at the 3 and 5 positions have greater steric hindrance than the triazine nitrogen atoms, which is more conducive to the twist angle of the donor connected to it, and thus more conducive to the performance of TADF materials. However, so far, only a few cases of TADF materials based on pyridine-3,5-dicarbonitrile have been reported (J. Mater. Chem., 2012, 22, 8922; J. Mater. Chem. C, 2018, 6, 6543; J. Phys. Chem. Lett. 2019, 10, 2669; CN109912564 A), and the efficiency and color code performance are far inferior to the reported optimal performance of TADF based on 1,3,5-triazine. Summary of the invention
[0009] In view of the above-mentioned deficiencies of the prior art, the present invention discloses an organic light-emitting material and a light-emitting device thereof. The patent discloses an organic light-emitting device application, including an anode, a cathode and an organic light-emitting layer composed of at least one light-emitting compound molecule as described herein sandwiched therebetween. The "sandwich" organic light-emitting device thus formed can obtain improved device performance by thermally activated reverse channeling RISC fluorescence, thereby providing an alternative to existing blue light fluorescent materials (first generation organic light-emitting materials), or obtaining high luminous efficiency similar to existing organic phosphorescent light-emitting materials but avoiding the problem of using expensive metals. The organic light-emitting device can emit a luminescent tone with very high purity, and achieve high brightness with high luminous efficiency and sufficiently long life. Since it does not contain precious metals, it also provides an organic light-emitting device with low cost production.
[0010] First, an organic light emitting diode device comprising
[0011] a) an anode,
[0012] b) a cathode,
[0013] c) The anode and the cathode contain multiple organic layers, and the multiple organic layers contain a light-emitting layer, which provides light emission through charge injection and effective transition; the transition is from the singlet state S1 to the ground state S0 and the triplet state T1 transitions to S1 through thermal activation and then to the ground state S0 to produce fluorescence.
[0014] In the above-mentioned organic light-emitting device, a pair of electrodes forming an anode and a cathode, and a multilayer structure device including a hole injection and transport layer, an emission layer, an electron injection and transport layer, etc., wherein the emission layer or the light-emitting layer is composed of one or two main materials and a light-emitting material compound, and the molar ratio of the light-emitting material compound in the light-emitting layer is 1-45%.
[0015] According to the organic light-emitting diode device, it is characterized in that the energy gap between T1 and S1 of the light-emitting material in the light-emitting layer calculated by Gaussian is less than 0.3 eV.
[0016] According to the organic electroluminescent diode device, it is characterized in that the light-emitting material compound in the light-emitting layer is represented by the following general formula 1.
[0017]
[0018] Wherein R is selected from alkyl, alkoxy, and all or part of the hydrogen on the alkyl and aryl groups may be substituted with deuterium;
[0019] Ar is selected from an aromatic ring, wherein the aromatic ring is a monocyclic ring, a condensed aromatic ring and a condensed heterocyclic aromatic ring, such as phenyl, naphthyl, anthracenyl, phenanthrenyl, fluorenyl, pyridinyl, indolyl, quinolyl, isoquinolyl, acridinyl, phenazinyl and phenanthridinyl; all or part of the hydrogens on Ar may be substituted with deuterium;
[0020] Q is selected from aromatic amines, fused aromatic amines, fused heterocyclic aromatic amines, carbazole, phenazine, phenoxazine, phenothiazine, dihydroacridine, benzothiophene, dibenzothiophene, benzofuran, dibenzofuran, benzothiazole, benzoxazole, and substituted aromatic amines, fused aromatic amines, fused heterocyclic aromatic amines, carbazole, phenazine, phenoxazine, phenothiazine, dihydroacridine, benzothiophene, dibenzothiophene, benzofuran, dibenzofuran, benzothiazole, benzoxazole; Q is bonded to the substituted benzene ring through a CC bond or a CN bond;
[0021] All or part of the hydrogen atoms in the compounds defined by the general formula 1 may be replaced by deuterium.
[0022] For ease of understanding, some typical compounds are given below, and exemplary compounds include but are not limited to the following compounds:
[0023]
[0024]
[0025]
[0026]
[0027]
[0028] The application of the material of the present invention to an organic light-emitting device is described in detail below. The organic light-emitting device of the present invention is an organic light-emitting device having at least one pair of electrodes, wherein at least one electrode comprises a transparent or semi-transparent anode or cathode, and one or more layers comprising organic compounds are between the electrodes (anode and cathode), wherein at least one layer of the layers comprises an organic compound selected from the compounds represented by Formula 1. Preferred examples of the organic light-emitting device of the present invention are Figure 1 , Figure 2 shown.
[0029] In fact, the OLED device shown includes the following functional layers:
[0030] 1: Substrate 101
[0031] 2: The substrate is covered with a conductive indium tin oxide coating ITO anode 101
[0032] 3: Luminous layer 104
[0033] 4: Conductive cathode 107
[0034] 5: Hole transport layer 103
[0035] 6: Electron transport layer 105
[0036] 7: Electron injection layer 106
[0037] 8: Hole injection layer 102
[0038] 9: Possible hole blocking layer
[0039] 10: Possible electron blocking layer
[0040] Figure 1 It is a cross-sectional view showing an example of an organic light-emitting device of the present invention. Obviously, by designing and selecting different light-emitting compounds of the present invention to adjust the energy band of the light-emitting compound of the light-emitting layer, the light-emitting color can be adjusted. Therefore, according to the organic light-emitting device, it is characterized in that the light-emitting device is blue light with a wavelength of 440-500nm, or green light with a wavelength of 510-545nm, or yellow light with a wavelength of 550-580nm, or the light-emitting device is red light with a wavelength of 590-640nm. On the other hand, the light-emitting compound of the present invention can also be used as an auxiliary main material, with an amount of 5-20% by weight, acting as a sensitizer, collecting the excitons (including singlet states and triplet states) generated by the main material, and does not emit light itself but transfers the excitons to the luminescent dopant to improve the device performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Cross-sectional view showing an example of an organic light-emitting device of the present invention
[0042] Figure 2 The UV-fluorescence spectrum of the organic light-emitting compound 1 of the present invention is shown as follows:
[0043] Figure 3 The electroluminescence spectrum of the organic light-emitting compound 1 of the present invention as a light-emitting material OLED (EL=450nm; CIEx=0.15, y=0.10) is shown. DETAILED DESCRIPTION
[0044] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with examples. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed below.
[0045] Example 1: Synthesis of Example Compound 1:
[0046]
[0047] Acetic anhydride (23.9 mL, 0.255 mol) was added dropwise to a glacial acetic acid (400 mL) solution containing (I) (30.3 g, 0.25 mol). The mixture was stirred until it cooled to room temperature. A glacial acetic acid solution containing bromine (40.75 g, 0.255 mol) was added dropwise to the above mixture, and the mixture gradually thickened. After the addition was complete, the reaction was continued for 30 min, and then the reaction solution was poured into 500 g of ice, filtered, washed with water, and dried to obtain 53.2 g of white granular product (II) with a yield of 88%.
[0048] Compound (II) (85 g) and NaOH (52 g) were dissolved in 200 mL of 57% ethanol solution to obtain a yellow solution. The solution was refluxed at 80° C. for 6 h, cooled to room temperature, diluted with 400 mL of water, stirred at room temperature for another two hours, filtered, and dried in vacuo to obtain compound (III) with a yield of 80%.
[0049] In a large beaker, add 225g crushed ice, 90mL concentrated hydrochloric acid and (III) (40.4g, 0.09mol), slowly add NaNO2 (15.1g, 0.097mol) aqueous solution (50mL) under stirring, keep the reaction temperature below 5°C during the addition. After the addition is complete, continue stirring for 15min, then slowly add KI (16g, 0.096mol) aqueous solution (120mL) to the reaction solution, the solution color immediately changes from yellow to brown, and the volume expands rapidly. After the addition is complete, continue the reaction for 30min, then add sodium thiosulfate saturated aqueous solution to the reaction solution, extract three times with dichloromethane, merge the organic phase, spin dry, and obtain the oily product (IV) by silica gel column purification (PE), with a yield of 70%.
[0050] Compound (IV) (10.0 g, 32.15 mmol), carbazole (5.37 g, 32.15 mmol), copper powder (2.47 g, 38.59 mmol), potassium carbonate (13.31 g, 96.46 mmol) and 100 DMF were added to the flask in sequence, replaced with nitrogen three times, and then reacted for 24 hours at 130°C under nitrogen protection. After the reaction, 200 mL of dichloromethane was added to the reaction solution, filtered with diatomaceous earth to remove insoluble impurities, dichloromethane was removed under reduced pressure, the remaining solution was poured into water, filtered, and the filter cake was purified with a silica gel column (PE / DCM=10 / 1) to obtain a crude product, which was dissolved with dichloromethane and reversely precipitated with methanol to obtain 6.3 g of white solid compound (V), with a yield of 56%.
[0051] Compound (V) (4.8 g, 13.7 mmol) was dissolved in 30 mL of anhydrous THF, cooled to -78 °C under nitrogen protection, and n-butyl lithium (6 mL, 15.1 mmol) was slowly added dropwise under stirring. After the addition was completed, the temperature was maintained to continue the reaction for 1 hour, and then anhydrous DMF (3.0 g, 41.1 mmol) was slowly added dropwise. After the addition was completed, the temperature was maintained to continue the reaction for 30 min, and then the temperature was raised to room temperature and the reaction was continued for 2 hours, and then 1N hydrochloric acid (50 mL) was added to the reaction solution, extracted with dichloromethane, and dried by spin drying. The light yellow compound (VI) was purified by silica gel column with a yield of 72%.
[0052] Compound (VI) (2.6 g, 8.7 mmol), phenylacetonitrile (2.78 g, 19.1 mmol), ammonium acetate (6.7 g, 87 mmol) and 50 mL of acetic acid were added to the reaction flask in sequence and reacted under reflux for 16 hours. After the reaction was completed, the mixture was cooled to room temperature, 300 mL of dichloromethane was added to the reaction solution, and the acetic acid and water-soluble substances were washed with water to remove the organic phase, which was dried by rotation and recrystallized with 150 mL of toluene to obtain a light yellow solid (VII) with a yield of 85%.
[0053] Compound (VII) (3.6 g, 6.5 mmol) was dissolved in 30 mL of dichloromethane, and DDQ (1.77 g, 7.8 mmol) was added to the solution. The reaction was completed after stirring at room temperature for 6 hours. Then 300 mL of dichloromethane was added to the reaction solution, washed with water, and the water-soluble matter was removed. The organic phase was spin-dried, and the target compound 1 was obtained by slurrying with methanol and filtering to obtain a white solid with a yield of 80%. Figure 2 It is the ultraviolet-fluorescence spectrum of the organic light-emitting compound 1 (BD175) of the present invention (PL=449 in film).
[0054] Example 2: Synthesis of other compounds:
[0055] Similarly, according to the above synthetic chemistry principles and the basic principles of general organic multi-step reactions, without violating the scope of the present invention, the following organic semiconductor material compounds were synthesized. The molecular weights and molecular fragments of the specific compounds listed were verified by mass spectrometry, and the specific summary is shown in Table 1 below:
[0056] Table 1: Compound synthesis and characterization
[0057]
[0058]
[0059]
[0060] Example 3. Application example in OLED device:
[0061] In a background vacuum up to 10 -5 In the multi-source evaporation OLED preparation equipment of Pa, the following device structure is used: ITO / 3% HATCN: mTDATA / TcTa / Host: 5% luminescent dopant / ET / LiF / Al, using different host materials and luminescent materials OLED light-emitting devices for comparison. Blue OLED uses BH: BD (5%) luminescent material, green OLED uses GH: BH (1:1 mixing ratio): luminescent dopant. The vacuum deposition speed of each organic layer and electrode is listed in Table 3.
[0062] Table 3: OLED device preparation conditions (doping wt concentration in the light-emitting layer 9%)
[0063]
[0064]
[0065] The known or common materials used in the experiment are shown in Table 4:
[0066]
[0067] The performance and comparison results of the fabricated OLED devices after testing are summarized in Table 5.
[0068] Table 5: OLED device performance (@10mA / cm2)
[0069]
[0070] The above shows that compared with the reference device B0 using the common electroluminescent doping material BD, the large-scale OLED light-emitting devices B1, B2, and B3 made of the blue light-emitting compounds 1, 10, and 18 described in the present invention show the effects of reduced operating voltage and improved current luminous efficiency. Figure 3 Compound 1 is used as a light-emitting doping material for OLED at 300Cd / m 2 EL emission spectrum at the time of the comparison. Similarly, compared with the reference device G0 using the commonly used electro-phosphorescent doping material Ir(mppy)3, the large-scale OLED light-emitting devices G1, G2, and G3 made of the green light-emitting compounds 4, 8, and 14 of the present invention show the effects of reduced operating voltage and improved current luminous efficiency. The use of compound 40 as an auxiliary host material can function as a traditional blue light OLED sensitizer, promote the comparison of the blue light emitting material BD to obtain improved efficiency, and extend the life span.
[0071] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the technical content disclosed above without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. An organic light-emitting diode device, comprising a) an anode, b) a cathode, c) The anode and the cathode contain multiple organic layers, and the multiple organic layers contain a light-emitting layer, and the light-emitting layer provides light emission through charge injection and effective transition; the transition is from the singlet state S1 to the ground state S0 and the triplet state T1 transitions to S1 through thermal activation and then to the ground state S0 to generate fluorescence; The luminescent layer is composed of one or two main materials and a luminescent material compound, and the molar ratio of the luminescent material in the luminescent layer is 1-45%; The luminescent material compound in the luminescent layer is the following compound:
2. The organic light emitting diode device according to claim 1, characterized in that: The energy gap between T1 and S1 of the luminescent material in the luminescent layer calculated by Gaussian is less than 0.3 eV.
3. The organic light emitting diode device according to claim 1, characterized in that: The organic electroluminescent diode device emits visible light with a wavelength of 440-640nm.
4. The organic light emitting diode device according to claim 1, characterized in that: The luminescent material compound in the luminescent layer can be used as an auxiliary host material of the luminescent layer or as a sensitizer material.
Citation Information
Patent Citations
Compound using cyano pyridine as core, and applications in OLED devices
CN109912564A
Compound using cyano pyridine as core, and applications in organic electroluminescent devices
CN109912565A
Cyanopyridine-containing compound and electroluminescent device comprising same
CN114644617A
Organic el material and organic el element employing same
US20190296246A1
KR20210010409A